Research progress on the relationship between free fatty acid profile and type 2 diabetes complicated by coronary heart disease - Liu, Xiuyan; Gong, Ming; Wu, Na (Frontiers in Endocrinology, 2024)
Patients with type 2 diabetes mellitus (T2DM) have a 2 to 3 times higher risk of cardiovascular disease compared to non-diabetic individuals, and cardiovascular disease has consistently been a leading cause of death among diabetic patients. Therefore, preventing cardiovascular disease in diabetic patients remains a significant challenge. In addition to classic indicators such as cholesterol and lipoproteins, previous studies have demonstrated that plasma level of free fatty acid (FFA) is closely related to the occurrence of atherosclerosis, particularly in T2DM patients. In recent years, with further research and advancements in testing technologies, the FFA profile has garnered widespread attention. The FFA profile includes many different types of FFAs, and changes in the plasma FFA profile and concentrations in T2DM patients may lead to the development of insulin resistance, causing damage to vascular endothelial cells and promoting the occurrence and progression of atherosclerosis. Furthermore, some FFAs have shown potential in predicting cardiovascular complications in T2DM and are associated with the severity of these complications. Here, we aim to review the changes in the FFA profile in T2DM and discuss the relationship between the FFA profile and the occurrence of vascular complications in T2DM.